Hubungan Antara Tayangan Youtube Sorabel dengan Pemenuhan Kebutuhan Informasi Warganet: Studi Korelasional pada Akun Media Sosial Youtube Sorabel - Dena Delaeni; Neni Yulianita (UNISBA Press, 2022)
Abstract. Social media is an online media that is used by users to represent themselves or interact, cooperate, communicate, share with other users, thus forming social bonds virtually. One of the social media that still has many visitors today is Youtube. Youtube is one of the sites that is widely used by audiences to find various kinds of information, especially in terms of fashion. One of the YouTube channels that discusses fashion is Sorabel. The purpose of this study is to find and analyze whether there is a relationship between the type of media, media content, and the exposure of Sorabel's Youtube show media with the fulfillment of netizens' information needs. The theory used in this study is the theory of uses and gratifications. The method used in this study is the correlational method. The sampling technique used in this study was simple random sampling. The population and samples taken by the researchers were netizens who watched and commented in one of Sorabel's Youtube shows entitled